Peningkatan Ketersediaan Waktu Operasi Pada Mesin Boiler Berdasarkan Down Time Dengan Pendekatan Metode Reliability Centered Maintenance (RCM) (Studi Kasus PT. Dian Swastika Sentosa, Tbk - Ahmad Zubair Sultan; Muhammad Arsyad Suyuti; Tanhar Bin Naim; Arya A. Amiruddin (Politeknik Negeri Ujung Pandang, 2020)
This study aims to (1) determine the subsystem or component that causes the main failure in boiler unit 2 and the effect on production efficiency. (2) Determine the maintenance interval at boiler unit 2 with the Reliability Centered Maintenance method. This research was conducted by processing downtime data from each sub-system or component, which was converted into time data between failures. Thus, testing of the distribution data is to determine the appropriate distribution. Based on the parameters obtained, it is used to determine the reliability function of each subsystem or component. Thus, the reliability value of each component over a certain period of time can be calculated. From the results of the research, the most damage has reliability including ballmill a (29.01%), ballmill b (37,250%), bottom ash a (41,604%), coal feeder a (35,282%), boiler (38,275%), hydraulic (20,236%), soot blower l3 (16,019%), coal feeder b (35,915%). So that reliability is focused on these components or subsystems. Then the maintenance time intervals are arranged as a group maintenance strategy to achieve the targeted system reliability.